1997
DOI: 10.1038/sj.ejcn.1600397
|View full text |Cite
|
Sign up to set email alerts
|

Increasing prevalence of underreporting does not necessarily distort dietary surveys

Abstract: Objectives: To study the magnitude of and trends in energy underreporting and to compare food consumption, nutrient intake and socioeconomic characteristics of underreporters to those of other Finnish adults. Design: Cardioavscular risk factor surveys in 1982 and 1992 using a 3 d food record. Underreporting was de®ned as energy intake lower than 1.27*BMR, since energy intake`1.27*BMR is improbable. Setting: Four areas in Finland, both rural and urban. Subjects: 1746 men and 1921 women, aged 25±64 y. Results: P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
147
5
4

Year Published

1997
1997
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(168 citation statements)
references
References 9 publications
10
147
5
4
Order By: Relevance
“…Misreporting of dietary intake can be general or specific, focusing on certain food groups. Previously, Finnish underreporters have been shown to selectively over-report the proportion of 'healthier' foods and under-report the intake of high-fat foods, 30 and similar phenomenon cannot be excluded in this study. Thus, it could be argued that simply the attention paid to certain dietary changes during dietary counselling could have induced selective misreporting by subjects and produced the reported changes in food consumption.…”
Section: Discussionmentioning
confidence: 72%
“…Misreporting of dietary intake can be general or specific, focusing on certain food groups. Previously, Finnish underreporters have been shown to selectively over-report the proportion of 'healthier' foods and under-report the intake of high-fat foods, 30 and similar phenomenon cannot be excluded in this study. Thus, it could be argued that simply the attention paid to certain dietary changes during dietary counselling could have induced selective misreporting by subjects and produced the reported changes in food consumption.…”
Section: Discussionmentioning
confidence: 72%
“…In the present study, 21.9% of the girls and 26.4% of the boys can be considered underreporters of total energy intake when comparing dietary energy intake with energy intake calculated by a formula of 1.39xBMR (basal metabolic rate) -2.24xBMR in boys and 1.30xBMR -2.10xBMR in girls (Torun et al, 1996). It has been shown that underreporting does not affect the proportions of energy nutrients (Hirvonen et al, 1997). To reduce the effect of underreporting, the micronutrient intakes were adjusted for total energy intake.…”
Section: Discussionmentioning
confidence: 99%
“…Those whose ratio was below 1.28, according to the recommendation of FAO/ WHO/UNU (1985) were regarded as having implausibly measured energy intakes for free-living persons, and were classi®ed as energy underreporters. The detailed analysis of underreporting based on this criteria has been reported elsewhere (Hirvonen et al, 1997).…”
Section: Methodsmentioning
confidence: 99%